Utility of Preoperative Upper Gastrointestinal Endoscopy in Reducing Post-Cholecystectomy Syndrome: An Analytical Cross-Sectional Study. - Kala C Mohan; Gopalaswamy, Vinaya; ghalige , Hemanth S; Raj, Preetham; Muniyappa, Sridhar; Suggaiah, Lakkanna; Tukaram, Arun Uttam; Purushottaman R (Student’s Journal of Health Research Africa, 2025)
Background: Cholelithiasis is a prevalent gastrointestinal disorder treated by laparoscopic cholecystectomy. However, nearly 40% of patients develop post-cholecystectomy syndrome (PCS), often due to undiagnosed non-biliary upper gastrointestinal (GI) pathologies. Objective: To determine the utility of preoperative upper gastrointestinal (GI) endoscopy in identifying concomitant GI disorders and its effect on the occurrence of PCS in patients undergoing laparoscopic cholecystectomy. Methods: This analytical cross-sectional study was conducted at ESIC Medical College and PGIMSR, Bengaluru, over 18 months. A total of 130 patients with symptomatic cholelithiasis were enrolled and divided into two groups of 65 each. Group I underwent laparoscopic cholecystectomy without prior endoscopy, while Group II underwent preoperative endoscopy, and the identified lesions were treated before surgery. Postoperative follow-up was carried out for three months, and the incidence of PCS was compared between groups using Fisher’s exact test. Results: Baseline demographic characteristics were similar between groups. Significant upper gastrointestinal pathology was detected in 55.4 % of patients in Group II, with gastroesophageal reflux disease (23.1 %), gastritis (13.8 %), and peptic ulcer disease (10.8 %) being common findings. At three-month follow-up, PCS symptoms were reported in 53.8 % of patients without endoscopy versus only 3.1 % of those who underwent preoperative endoscopy (p < 0.00001). The results demonstrate a strong association between preoperative endoscopic screening and reduced PCS incidence. Conclusion: Preoperative upper gastrointestinal endoscopy aids in detecting and managing coexisting upper GI disorders, thereby markedly reducing PCS. Routine or selective use of endoscopy is recommended in patients presenting with atypical pain, dyspepsia, or reflux symptoms before cholecystectomy. Further multicentric studies with longer follow-up are recommended to validate these findings and establish protocol-based implementation.